Development and Pilot Test of a Group Cognitive Behavioral Intervention for Women Recovering From Fistula Repair Surgery in Ethiopia - Gladstone, Tracy R. G.; Ugueto, Ana M.; Muleta, Mulu; Meshesha, Tsega M.; Ambaafris, Genet G.; Patwa, Mariya C.; Zhong, Cordelia; Buchholz, Katherine R. (Frontiers in Public Health, 2022)
Obstetric fistula is a serious complication that affects thousands of women in low-income countries. Women who suffer from obstetric fistulae are at risk of developing mental health problems, but to date most interventions have focused on repairing the physical consequences of fistulae through surgery. The goal of the current study is to develop an evidence-based intervention targeting symptoms of depression, anxiety, and trauma in women recovering from fistula repair surgery. First, hospital staff and patients awaiting surgery at a fistula hospital in Ethiopia participated in qualitative interviews to provide information on the mental health needs of women with fistulae, how the hospital tends to these women’s psychological needs, and the training needs of staff members. Data from these interviews were used to develop the COFFEE intervention (CBT with Obstetric Fistula for Education and Empowerment). COFFEE is a modular, group intervention that teaches psycho-education, behavioral activation, relaxation, problem solving, cognitive restructuring, and includes a trauma narrative. Patients then participated in an open trial of the COFFEE intervention at the University of Gondar Hospital. Five separate groups were conducted with 24 women who were enrolled post-fistula repair surgery. Women completed pre-treatment self-report questionnaires, participated in group sessions conducted by nurses (with 8 sessions delivered across 10-14 days), and were assessed post-treatment and at 3-month follow-up. Results indicate a significant reduction on depression and anxiety symptoms scores across the three time points (F (2, 40) = 68.45, p<.001 partial ɳ2 = .774). Additionally, there was a significant decrease in traumatic stress scores from baseline to post-treatment (F (1.10, 21.98) = 100.51, p<.001 partial ɳ2 = .834). Feedback forms completed by nurses and patients suggest the intervention was well received. Results of this open-trial suggest the COFFEE intervention is feasible, acceptable, and clinically beneficial to treat symptoms of depression, anxiety, and traumatic stress in women post-fistula repair surgery in a hospital setting.